EFEKTIVITAS PENGGUNAAN MODUL IPA DALAM PEMBELJARAN TATAP MUKA TERBATAS PADA SISWA KELAS IX MTs NEGERI 8 KAMPAR SELAMA PANDEMI COVID-19 (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the effectiveness of the limited face-to-face learning science module during the Covid-19 pandemic. The subjects of this study were students in grades IX.1 and IX.2 at MTs Negeri 8 Kampar. The number of students in class IX.1 is 29 students and class IX.2 is 28 students. The type of research used in this research is a pre-experimental design research with a one-shot case study design. Data collection techniques used in this study were tests and questionnaires. The data analysis technique used in this research is descriptive quantitative. The effectiveness of the developed module is viewed from the percentage of classical completeness, student learning completeness from competency indicators, and student responses related to the developed module. The instruments used are test sheets and questionnaire sheets. The results obtained in this study are that the developed module is effective in terms of the classical completeness percentage of 83.87% for class IX.1 and 84.37% for class IX.2. Completeness based on competence, students, and competencies possessed by students. The conclusion of this study is that the limited face-to-face learning science module is effectively applied to limited face-to-face learning during the Covid-19 pandemic as a learning mediaKeywords: The Effectiveness of Science Modules, Covid-19 Pandemic, Limited Face-to-Face Learning